Leading for Change: School Leader Advocacy for Undocumented Immigrant Students. Issue 1 (2nd January 2018) - Crawford, Emily R.; Walker, Danielle; Valle, Fernando
ABSTRACT: School leaders can ally with other educational stakeholders to encourage undocumented student persistence in Pk-12 schools. We explore (1) how school leaders create systems of support for undocumented and newly arrived immigrant students, and (2) how school leaders interpret and implement policies or school structures that affect student educational access. Border crossing theory guides our examination of how school leaders traverse and transgress borders that can impede students' education. This embedded case study included interviews with nine administrators working on the US-México border. The study finds that leaders expected to make a difference in students' lives by focusing on relationships and programming, committing to equity, and resisting deficit thinking about students and their families.